Dynamic effects of dietary protein restriction on body weights, food consumption, and protein preference in C57BL/6J and Fgf21‐KO mice. Issue 3 (11th March 2022) - Torres, Francis; Khan, Shahjalal; Fernandez‐Kim, Sun Ok; Spann, Redin; Albarado, Diana; Wagner, Thomas J.; Morrison, Christopher D.; Soto, Paul L.
Abstract : Single‐case experimental designs (SCEDs) are rarely used in behavioral neuroscience despite their potential benefits. The current study used a SCED to evaluate the effects of dietary protein restriction in C57BL/6J and Fgf 21‐knockout (KO) mice on body weight, food consumption, and protein preference and changes in those outcome measures were quantified using multilevel linear models. In C57BL/6J mice, rate of weight gain was lower and food consumption and protein preference higher during periods of low (4% kcal) protein diet feeding compared to periods of normal (18% kcal) protein diet feeding. In Fgf 21‐KO mice, who do not produce the liver‐derived hormone FGF21, rate of weight gain and protein preference were not substantially affected by diet although food consumption was slightly higher during periods of low protein diet than periods of normal protein diet. These results demonstrate that protein restriction dynamically regulates physiological and behavioral responses at the individual mouse level and that FGF21 is necessary for those responses. Further, the current results demonstrate how a SCED can be used in behavioral neuroscience research, which entails both scientific and practical benefits.